PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR), GREEN INNOVATION, DAN REPUTASI PERUSAHAN TERHADAP KINERJA KEUANGAN (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Naia Fitrah Alia; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effects of Corporate Social Responsibility (CSR), Green Innovation, and Corporate Reputation on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange in 2022-2024. This study is grounded in stakeholder theory.The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Purposive sampling was used in selecting the research sample, resulting in 195 research samples for three consecutive years (2022–2024).The results of the analysis indicate that Corporate Social Responsibility does not have a significant direct effect on Financial Performance. Meanwhile, Green Innovation has a positive and significant effect on Financial Performance, and Corporate Reputation also has a positive and significant effect on Financial Performance.